Control of the micrometric scale morphology of silicon nanowires through ion irradiation-induced metal dewetting. (August 2016) - Lo Savio, R.; Repetto, L.; Guida, P.; Angeli, E.; Firpo, G.; Volpe, A.; Ierardi, V.; Valbusa, U.
Abstract: We propose ion-induced dewetting of Au thin films as a mechanism to modify and control the morphology of Si nanowires formed through metal-assisted chemical etching. We show that the patterns formed upon irradiation resemble those typical of dewetting phenomena, with a characteristic length in the nanometer range. Irradiated Au films are then used as a template for the fabrication of Si nanowires, and we show that a long-range order exists also in etched substrates, although at much longer length scales in the micrometer range. Investigation of the optical properties reveals that the Si nanowires emit broadband photoluminescence peaked at 700 nm. The proposed synthesis method allows tuning the morphological features of the nanowire bundles at the nanoscale without affecting the optical properties. This approach can be exploited for the engineering of nanowires-based devices where the morphological features become important. Highlights: Patterns formed through dewetting of Au film have nm-range characteristic lengths. Dewetted films are used as templates to fabricate Si nanowires. Morphology of nanowires bundles is characterized by µm-range characteristic lengths. The luminescence emission wavelength does not depend on the morphology.